2012
DOI: 10.1186/1746-6148-8-132
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of avian influenza virus H5 plasmid DNA with chicken IL-15 and IL-18 enhanced chickens immune responses

Abstract: BackgroundDNA vaccines offer several advantages over conventional vaccines in the development of effective vaccines against avian influenza virus (AIV). However, one of the limitations of the DNA vaccine in poultry is that it induces poor immune responses. In this study, chicken interleukin (IL) -15 and IL-18 were used as genetic adjuvants to improve the immune responses induced from the H5 DNA vaccination in chickens. The immunogenicity of the recombinant plasmid DNA was analyzed based on the antibody product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…IL18 can regulate both innate and adaptive immune responses through its effects on T cells (4,7,28), NK cells (29,30), macrophages (31), and DCs (32). Systemic administration of IL18 had little antitumor activity in several preclinical animal models (33).…”
Section: Discussionmentioning
confidence: 99%
“…IL18 can regulate both innate and adaptive immune responses through its effects on T cells (4,7,28), NK cells (29,30), macrophages (31), and DCs (32). Systemic administration of IL18 had little antitumor activity in several preclinical animal models (33).…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 is a strong IFN-␥-inducing factor that enhances immune responses when used as an adjuvant. The concept of using IL-18 to boost immune responses after vaccination has been investigated for chicken vaccines (23,24,32,(36)(37)(38). Hung et al (21) described that the full-length and mature chicken IL-18 purified recombinant protein effectively enhanced cell-mediated and humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that ChIL-18 is expressed in nonchicken-derived cells (21,32). However, there are no documents showing whether ChIL-18 plasmid expresses IL-18 in chicken cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant chicken IL-18 (chIL-18) protein also has the ability to act as a potent adjuvant when co-administered with cell-cultured Newcastle disease vaccine (14). Recently, it is reported that chicken IL-15 and IL-18 used as genetic adjuvants improve the immune responses induced from the AIV H5 DNA vaccination in chickens as evaluated by antibody production, T cell responses and cytokine production (15). However, the properties and practical application of chIL-18 remain largely uninvestigated as of yet.…”
Section: Introductionmentioning
confidence: 99%